Lathyrus genetic resources in Asia: Proceedings of a regional workshop, Raipur, India, 27-29 December 1995 - Arora, R.K.; Mathur, P.N.; Riley, K.W.; Adham, Y.; International Plant Genetic Resources Institute (1996)
The proceedings contain the recommendations of the participants from the major Lathyrus growing countries in Asia to form a small network aimed at effectively conserving, sharing, documenting and using the available diversity of this hardy legume crop. The proceedings also contain information on the status of Lathyrus genetic resources, utilization and research in the participating countries.For the past decade, this hitherto neglected crop has received intense international attention. It is well recognized that farmers' varieties of this crop can tolerate flooded conditions after sowing and drought conditions later in growth. The species possesses unique adaptation as a post-rice crop across much of South Asia. Variants have been found with high quality and yields of grain and fodder. Nevertheless, these advatanges were overshadowed by the presence of a crippling neurotoxin known as ODAP found in the seed of L. sativus. Genetic stocks with very low levels of neurotoxin have now been identified both through conventional breeding and through somatic mutation. Attempts to rapid methods of analysis of neurotoxin levels in plant tissue have been developed and rapid progress in breeding these lines reported. Such progress makes the aims of the present workshop even more pertinent. There is now the opportunity to incorporate the low neurotoxin trait into a broad range of genetic diversity possessing local adaptation, pest and disease resistance, and high yield and quality of grain and fodder, while maintaining the essential resistance to stress conditions that give Lathyrus its unique advantage.